The place of the Auffassung within the dispute over the essence of fantasy: Husserl’s elaboration and self-criticism - Guerrero Cordero, Felipe (Resonancias. Revista de Filosofía, 2020)
This paper addresses to expose in a synthetic way the place that has the scheme act/content of apprehension in the thematic of the essence of fantasy and its subsequent crisis. The question that leads us is the one that interrogates the limits of the act/content scheme. For this we will have three moments. In the first place you will have a clarification of the notion of apprehension [Auffassung] from the Logical Investigations. The second moment seeks to account for the role of apprehension on the road to elucidating the peculiar essence of fantasy [Phantasie] in the third part of the Hauptstücke aus der Phänomenologie und Theorie der Erkenntnis. The third and final objective is present what puts the act/content scheme in check and prepare the way towards understanding fantasy as an intentional modification.